Well-Being over the Life Span: Semiparametric Evidence from British and German Longitudinal Data - Christoph Wunder; Andrea Wiencierz; Johannes Schwarze; Helmut Küchenhoff; Sara Kleyer; Philipp Bleninger (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper applies semiparametric regression models using penalized splines to investigate the profile of well-being over the life span. Splines have the advantage that they do not require a priori assumptions about the form of the curve. Using data from the British Household Panel Survey (BHPS) and the German Socio-Economic Panel Study (SOEP), the analysis shows a common, quite similar, age-specific pattern of life satisfaction for both Britain and Germany that can be characterized by three age stages. In the first stage, life satisfaction declines until approximately the fifth life decade. In the second age stage, well-being clearly increases and has a second turning point (maximum) after which well-being decreases in the third age stage. Several reasons for the three-phase pattern are discussed. We point to the fact that neither polynomial functions of the third nor the fourth degree describe the relationship adequately: polynomials locate the minimum and the maximum imprecisely. In addition, our analysis discusses the indistinguishability of age, period, and cohort effects: we propose estimating age-period models that control for cohort effects including substantive variables, such as the life expectancy of the birth cohort, and further observed socioeconomic characteristics in the regression.
Keywords: C14; C23; D10; I31; 330; subjective well-being; life satisfaction; semiparametric regression; penalized splines; age-period model; age-cohort model